Is There a "July Effect" in Oncologic and Benign Gynecologic Surgery? [17Q]. (May 2018) - Mastroyannis, Spyridon A.; Buckingham, Lindsey; Brensinger, Colleen; Latif, Nawar; Haggerty, Ashley; Ko, Emily
Abstract : INTRODUCTION: The "July Effect" is a phenomenon previously described as increased complication rates during times of trainee transition. This study aimed to evaluate the effect of academic quarter on perioperative outcomes for gynecologic surgery patients. METHODS: Patients who underwent gynecologic surgery with trainee involvement were identified in the National Surgery Quality Improvement Program (NSQIP) database between July 1, 2006 and June 30, 2012. Benign and oncologic cases were collected. Academic quarters of the year were defined as Q1: Jul-Sep, Q2: Oct-Dec, Q3: Jan-Mar and Q4: Apr-Jun. Major complications included surgical site infection (SSI), myocardial infarction, pulmonary embolism, stroke, deep vein thrombosis (DVT), and re-intubation. Kruskal-Wallis and Chi square tests were performed. Two-sided alpha with p<0.05 was designated as significant. RESULTS: Of 104, 012 gynecologic surgeries, 25, 290 (21, 086 benign; 4204 oncologic) had confirmed resident involvement. In benign cases, re-operation rate was highest in Q1 vs Q2-4 (1.8% vs 1.1-1.6%; P=0.043); length of stay (LOS) in days was also increased in Q1 (2.0 vs 1.6-1.8, p=0.0149). In Q3, higher rates of organ space SSI and emergent cases were observed: (1.0% vs 0.5-0.6%, P=0.0197 and 4.3% vs 3.4-3.9%, p=0.0321 respectively). For oncology patients, only LOS was increased for Q1 (4.8 vs 3.8-4.1, p<0.0001). CONCLUSION: In this national sample, first academic quarter was associated with increased LOS and re-operation, but not overall severe complication rate in benign gynecologic surgeries. In oncology, LOS was increased, but overall complications, re-operation and readmissions were not. The "July Effect" did not hold true for gynecologic surgery with trainee involvement.